Oral history of Bulacan public libraries project - Jaime, Romel R. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Individual histories of public libraries in the different provinces, cities, and towns in the Philippines need to be recorded so that the important role they have played in the community where they are located will be highlighted, appreciated, and preserved. This project's goal is to satisfy at least a fraction of that need. Specifically, this project aims to: 1. gather, record, and compile the oral history of Bulacan public libraries before they are lost forever; 2. create and preserve source materials for future researchers of the history of said public libraries; and 3. make these oral histories available to public.